Pengembangan Potensi Wisata Pemancingan Kolam Ikan Tawar dan Penyuluhan Ekologis serta Kesehatan Masyarakat - Rita Marsuci Harmain; Juliana Juliana; Rahim Husain; Nur Izzah Fuad (JURNAL PENGABDIAN PAPUA, 2025)
The purpose of community service is to provide knowledge and skills for the development of pond fishing tourism and freshwater fish farming, as well as ecological and public health education in Biyonga Village, Limboto District, Gorontalo Regency. The methods used are mentoring to provide knowledge and skills for the development of fishing tourism, knowledge and strategies for improving freshwater fish farming businesses, and providing ecological and public health education. Additionally, supplementary activities include training in the production of diversified post-harvest products based on local potential to increase the selling value of freshwater fish farming, thereby improving the economy and income of the community in Biyonga Village. The results of the activity were an understanding of knowledge and skills in developing pond fishing tourism and freshwater fish farming, as well as awareness and commitment to preserving the forest ecosystem and sustainable watersheds. There is awareness among the community to maintain health and increase knowledge and skills in the production of post-harvest products from freshwater fish farming based on local potential, which has an impact on increasing community income in Biyonga Village.